The effect of little dentist education on the knowledge level of dental and oral health of elementary school children in Badung: Pengaruh edukasi dokter gigi kecil terhadap tingkat pengetahuan kesehatan gigi dan mulut anak sekolah dasar di Badung - Ni Putu Ayu Ratnasari; Putri Rejeki; Luh Ayu Wayan Rahaswanti; Kadek Asri Asmita Pradnyana Putri (Makassar Dental Journal PDGI Makassar, 2024)
Oral health problems limit an individual's ability to speak, chew, bite, smile, and psychosocial well-being. Riskesdas of Bali Province in 2018 stated that 51.72% of children aged 5-9 years and 34.19% of children aged 10-14 years had tooth decay. Efforts to overcome dental health problems can be implemented through the School Dental Health Effort programme by training health cadres such as little dentists. This study aims to determine the difference in the level of oral health knowledge of elementary school children in Ungasan Village before and after being educated by a little dentist, using a pre-experimental study design and a one-group pretest-posttest design. The samples were students at SDN 5 Ungasan, SDN 7 Ungasan, and SDN 8 Ungasan who met the inclusion criteria, by using purposive sampling technique. As a result, there is a difference between the level of knowledge, namely the average level of knowledge of children's oral health before being given education by a little dentist is in the moderate category, while there is an increase of knowledge after education to the good category. It is concluded that there is a difference between the level of knowledge of elementary school children before and after being given education by small dentists.